A Potent and Protective Human Neutralizing Antibody Against SARS-CoV-2 Variants - Shan, Sisi; Mok, Chee Keng; Zhang, Shuyuan; Lan, Jun; Li, Jizhou; Yang, Ziqing; Wang, Ruoke; Cheng, Lin; Fang, Mengqi; Aw, Zhen Qin; Yu, Jinfang; Zhang, Qi; et al. (Frontiers in Immunology, 2021)
As SARS-CoV-2 variants continues to emerge and spread around the world, antibodies and vaccines to confer broad and potent neutralizing activity are urgently needed. Through isolation and characterization of monoclonal antibodies (mAbs) from SARS-CoV-2 infected individuals, we identified one antibody, P36-5D2, capable of neutralizing major SARS-CoV-2 variants of concern. Crystal and cryo-EM structure analysis revealed that P36-5D2 targeted to a conserved epitope on the receptor-binding domain of spike protein, withstanding the three key mutations K417N, E484K and N501Y found in the variants that responsible for escape from many potent neutralizing mAbs including some already approved for emergency use authorization (EUA). A single intraperitoneal (IP) injection of P36-5D2 as a prophylactic treatment completely protected animals from challenge of infectious SARS-CoV-2 Alpha and Beta. Treated animals manifested normal body weight and devoid of infection associated death up to 14 days. Substantial decrease in infectious virus in the lungs and brain as well as reduced lung pathology were found in these animals compared to the controls. Thus, P36-5D2 represent a new and desirable human antibody against current and emerging SARS-CoV-2 variants.